Upgrading the wood vinegar prepared from the pyrolysis of biomass wastes by hydrothermal pretreatment. (1st April 2022) - Xu, Jiaqing; Zhang, Shouyu; Shi, Yue; Zhang, Peizheng; Huang, Dongdong; Lin, Chunyu; Wu, Yuxin
Abstract: Hydrothermal pretreatment (HT) is an effective method to upgrade biochar pellets, while little attention is paid to wood vinegar (WV), the byproduct of biochar pellets production. Therefore, Chinese fir sawdust (FS) and cotton stalk (CS) were hydrothermally pretreated first at 180–280 °C and then pyrolyzed at 350 °C in the study. The effect of hydrothermal pretreatment on the properties of biomass was evaluated by the Van Soest method and thermogravimetric method. The yield, pH, density, and composition of WV were analyzed. The results showed that hemicellulose and cellulose were completely decomposed at HT temperatures of 230 °C and 280 °C respectively. The removal of hemicellulose and the enrichment of cellulose and lignin in the samples pretreated before 230 °C result in a higher density and lower pH of WV, while the yield only increases before 200 °C. Compared with CS samples, the higher content and reactivity of cellulose, especially amorphous cellulose, and lignin in FS samples results in the higher yield of the organic compounds in FSWV. With HT temperature increasing to 230 °C, the content and yield of acids in FSWV/CSWV shows a declining trend, and the content and yield of phenols, ketones, and aldehydes increase. HT pretreatment below 230 °C can upgrade WV. Highlights: Evolution of the components in FS and CS during HT pretreatment is given. Relationship between the components of FS/CS samples and WV is gained. Less hemicellulose and more amorphous cellulose and lignin improve WV quality. FS with higher reactivity is more suitable for WV preparation than CS. WV can be upgraded from the biomass HT pretreated below 230 °C.